Operative Versus Nonoperative Management of Pyogenic Flexor Tenosynovitis: An Analysis of the National Readmissions Database - Justin D. Sawyer, MD; Justin Davis, MD; Steven Scaife, MS; Michael W. Neumeister, MD; Timothy H.F. Daugherty, MD (Journal of Hand Surgery Global Online)
Purpose: The purpose of this study was to use a national database to determine if either surgical or nonsurgical management of pyogenic flexor tenosynovitis (PFT) led to specific superior outcomes. Methods: International Classification of Diseases, Tenth Revision codes were used to identify patients admitted with PFT from the National Readmissions Database for the years 2016–2019. All patients had been admitted initially and treated with either surgical or nonsurgical management. Baseline characteristics were determined, and in those who were readmitted, the top 10 diagnoses of 90-day readmissions were identified. Risk factors for readmission were identified using a regression analysis. Ninety-day readmission rates, amputation rates, and length of stay between the groups were compared, as these are outcomes that can be reviewed from the database. Results: The overall 90-day readmission rate was 13.25%. Infectious complications from the original diagnosis of PFT were the leading causes of readmission. Variables associated with 90-day readmission were higher Charlson comorbidity index, hypertension, Medicaid insurance, longer initial length of hospital stay, tobacco use, and nonsurgical management. Ninety-day readmission rates and amputation rates were higher in the nonsurgical group. Conclusions: In patients with PFT, surgical intervention may prevent hospital readmissions and reduce the likelihood of amputation. Readmission is more likely in patients with more medical comorbidities, tobacco users, and lower socioeconomic status. Type of study/level of evidence: Prognosis IIC.